EFEKTIVITAS PROGRAM INTERVENSI FISIK DAN MENTAL DALAM PENGENDALIAN STRES KERJA PERAWAT DI IGD RUMAH SAKIT BHAYANGKARA TK. I RADEN SAID SUKANTO - Widhi Nurfadillah (2023)
Work stress is a risk to the health and safety of workers when the work is done beyond their capacity, resources and talents over a long period of time. Nurse work stress that is not handled will lead to poor performance. So it is necessary to have special actions to overcome the work stress of nurses. The application of evidence based practice aims to determine the effect of physical and mental intervention programs in overcoming nurse work stress. The subjects of this evidence based practice application are nurses who experience strong maladaptive stress in the IGD Room of Bhayangkara Hospital TK.I Raden Said Sukanto. The implementation was carried out for four consecutive days from 14 to 17 March 2023. The results of the implementation of the physical and mental intervention program showed that there was a decrease in the value of work stress for nurses. Based on the results of the paired t-test conducted by the author, the results showed a p-value <0.05. This value indicates that physical and mental interventions have a significant effect on the work stress of nurses in the IGD Room of Bhayangkara Hospital TK.I Raden Said Sukanto. Nurses are expected to be able to use this intervention in everyday life to reduce their stress.